Influence of theobromine in feed on larval growth and survival in Tenebrio molitor - Matthieu Bourdarias; Sofie Landschoot; Mia Eeckhout; Myriam Hesta (PLoS ONE, 2025)
With the growing interest in using insects as a sustainable protein source for human and animal consumption, identifying suitable feedstuffs is crucial for their rearing. Although Tenebrio molitor larvae can valorise food industry byproducts, the presence of certain compounds may limit this potential. This study assesses the impact of theobromine, a methylxanthine found in chocolate, on the growth and mortality of Tenebrio molitor larvae. The aim was to evaluate the feasibility of rearing mealworms on byproducts and former foodstuffs from the biscuit, confectionery and chocolate industries. Larvae were fed varying concentrations of theobromine (up to 5000 mg/kg) in their diet under controlled laboratory conditions. Weight and mortality were monitored until 10% pupation was observed. Results indicated that concentrations up to 600 mg/kg of theobromine had no significant effect on overall larval growth. Concentrations up to 1600 mg/kg did not significantly affect final weight but caused weight differences during growth, and only exposure to 5000 mg/kg appeared to increase mortality. These findings suggest that exceeding a threshold of theobromine influences larval growth, and high exposure could lead to increased mortality. This study expands the potential range of byproducts, including those containing chocolate, that could be incorporated into mealworm feed formulation.